Synthesis and Characterization of Polyvinyl Alcohol Based Membrane - Janudin, Fahmy Fadhyllah; Abu Bakar, Amiruddin Ali; Fauzi, Basirah; Nurul Izzati Mohd Ismail, (Multidisciplinary Applied Research and Innovation, 2023)
Poly (vinyl alcohol) (PVA) is a polymer that, since the 1970s, has been a popular choice for membrane fabrication due to its excellent film-forming characteristics, outstanding chemical and mechanical stability, and tunable hydrophilicity. This project aim is to develop hydrophilic membrane using Polyvinyl Alcohol, Chitosan and Starch as the major ingredients and optimize the formulation of membrane using response surface methodology hence characterize the PVA-based membranes in term of physical, chemical and mechanical properties. The characterization of membrane were done by analysis using Fourier-Transform Infrared to identify functional group and chemical bonds involved and also used Scanning Electron Microscopy (SEM) to identify its topology or morphology of the membrane. Through response surface methodology (RSM), membrane characterization has been done using two responses which are swelling index and WVTR and the function of these response are to identify how much the membrane could absorb water and identify how much of water or vapour could pass through the membrane and thus our membranes show high efficiency means the R2 value obtained is higher than 85% which is 0.9164 of R2 value (91.64%) for response 1; swelling index and 0.8951 of R2 value (89.51%) for response 2: WVTR and proven that the membrane is hydrophilic and very selective to water.